Is Serum Lactate a Good Predictor of Mortality in Children Aged 2 Months to 5 Years With Pneumonia in Central Vietnam - Son Bui-; Trang Nguyen-; Anh Nguyen-; Nguyen Thi Kim Hoa; Dung Pham-Van (SAGE Publishing, 2021)
Pneumonia is a major cause of morbidity and mortality in children globally. Lactate, a product of anaerobic cellular metabolism, has been used as an indicator of poor tissue oxygenation and cellular hypoxia. Our objective was to determine whether serum lactate concentration at hospital admission predicted mortality in children aged 2 months to 5 years with pneumonia. Two hundred and eighty-one pediatric patients admitted to the Department of Pediatrics of a provincial hospital with WHO-defined pneumonia and severe pneumonia were included; of whom, 8 died during hospital stay. The median serum lactate concentration was 4.8 mmol/l (IQR 2.6-6.9) among children who died and 3.6 mmol/l (IQR 2.8-4.3) among children who survived ( P > .05); 4.1 mmol/l (IQR 2.7-4.7) among children with severe pneumonia and 3.5 mmol/l (IQR 2.8-4.3) among children with pneumonia ( P > .05). Serum lactate concentration had a low value in predicting pneumonia-related mortality (AUC 0.68, 95% CI 0.62-0.73); and the concentration cut-off of >4.06 mmol/l had the best sensitivity and specificity (75% and 68.9%, respectively) with a 2.4-fold risk of death (LR+ 2.4; 95% CI 1.6-3.7). Although hyperlactatemia was associated with severity and mortality in children 2 months to 5 years of age with pneumonia, its benefit was unclear.